2000
DOI: 10.1103/physrevd.61.105019
|View full text |Cite
|
Sign up to set email alerts
|

Bags, junctions, and networks of BPS and non-BPS defects

Abstract: We investigate several models of coupled scalar fields that present discrete Z_2, Z_2 x Z_2, Z_3 and other symmetries. These models support topological domain wall solutions of the BPS and non-BPS type. The BPS solutions are stable, but the stability of the non-BPS solutions may depend on the parameters that specify the models. The BPS and non-BPS states give rise to bags, and also to three-junctions that may allow the presence of networks of topological defects. In particular, we show that the non-BPS defects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
125
0
13

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(142 citation statements)
references
References 50 publications
4
125
0
13
Order By: Relevance
“…In Ref. [21,22,23,24] it was shown that this bound can be obtained in two-field models defined by the potential…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In Ref. [21,22,23,24] it was shown that this bound can be obtained in two-field models defined by the potential…”
Section: Introductionmentioning
confidence: 90%
“…[21] one introduces a simple model, described by two real scalar fields, which support both Ising and Bloch walls -see, e.g., Ref. [22,23,24] for further details on the two-field model, and on Ising and Bloch walls. The approach introduced in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…We will work with BPS solutions, because they are classically stable at least at the level of the classical field model in 1 + 1 space-time dimensions [25]. In this case it can be shown that the solutions of the BPS equations…”
Section: Exact Solutionsmentioning
confidence: 99%
“…For this class of systems, one can show that the minimum energy configurations can be obtained from the equivalent system of coupled first-order differential equations [30] …”
Section: Introductionmentioning
confidence: 99%
“…where i and i are the values of the fields at the ith vacuum state of the model [30]. Instead of applying the usual trial-orbit approach [31], we note that it is possible to write the following equation…”
Section: Introductionmentioning
confidence: 99%